2001
DOI: 10.1248/bpb.24.1316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Ca2+-Dependent Protein Kinase from Rice Root: Differential Response to Cold and Regulation by Abscisic Acid.

Abstract: Plants can respond to a variety of biotic and abiotic signals or factors that affect their growth and development. Although the responses to these signals and factors in plants have been extensively studied at physiological and biochemical levels, the perception and intracellular transmission mechanisms remain largely unknown. Under natural growth conditions, plants do encounter various stress conditions such as drought, salinity, and high or low temperature, which have profound effects on their growth and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Many other examples of multiple stimuli inducing the expression of individual CPKs are known. Increased steady-state transcripts, abundance, or activities of various CPKs in response to low-temperature, ionic, osmotic, water deficit, wounding, and elicitor treatments implicate their possible involvement in signaling response networks for these environmental stimuli (Botella et al, 1996;Pestenácz and Erdei, 1996;Yoon et al, 1999;Komatsu et al, 2001;Murillo et al, 2001;Romeis et al, 2001;Chico et al, 2002;Llop-Tous et al, 2002). The remaining challenge is to determine the specific contribution to signaling pathways made by each individual CDPK and the degree of overlap or redundancy among these different signaling cascades.…”
Section: Mccpk1 Is Transiently Induced By Salinity and Water Deficit mentioning
confidence: 99%
See 1 more Smart Citation
“…Many other examples of multiple stimuli inducing the expression of individual CPKs are known. Increased steady-state transcripts, abundance, or activities of various CPKs in response to low-temperature, ionic, osmotic, water deficit, wounding, and elicitor treatments implicate their possible involvement in signaling response networks for these environmental stimuli (Botella et al, 1996;Pestenácz and Erdei, 1996;Yoon et al, 1999;Komatsu et al, 2001;Murillo et al, 2001;Romeis et al, 2001;Chico et al, 2002;Llop-Tous et al, 2002). The remaining challenge is to determine the specific contribution to signaling pathways made by each individual CDPK and the degree of overlap or redundancy among these different signaling cascades.…”
Section: Mccpk1 Is Transiently Induced By Salinity and Water Deficit mentioning
confidence: 99%
“…Pharmacological studies have implicated CDPK participation in fungal pathogen defense (Romeis et al, 2000), wound signaling (Schaller and Oecking, 1999), and osmotic stress signaling (Pestenácz and Erdei, 1996;Taybi and Cushman, 1999). Furthermore, the expression patterns or activity changes of some CDPKs have suggested functional roles in low-temperature, ionic, osmotic, or water deficit stress signaling (Urao et al, 1994;Botella et al, 1996;Pestenácz and Erdei, 1996;Yoon et al, 1999;Komatsu et al, 2001;Chico et al, 2002;Llop-Tous et al, 2002), light responses (Pagnussat et al 2002), jasmonate signaling , and elicitor-induced signaling (Yoon et al, 1999;Murillo et al, 2001;Romeis et al, 2001).…”
mentioning
confidence: 99%
“…Drought, salt, cold, light, and hormones can influence the expression or activity of various CDPKs in plants (Sopory and Munshi, 1998). Increased CDPK activity and Ca 2+ -dependent protein phosphorylation were observed in rice seedlings exposed to cold (Li and Komatsu, 2000;Komatsu et al, 2001) and hormone treatment (Kawasaki et al, 1993;Karibe and Komatsu, 1997;Yang and Komatsu, 2000). Using sense and antisense transgenic rice, CDPKs were identified as signaling components downstream of both the gibberellin (GA)-binding protein and the brassinosteroid receptor (Sharma et al, 2001;Sharma and Komatsu, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A different regulation by plant hormones was observed in rice roots, where the activity of a 45 kDa CDPK decreased previously by cold was recovered by exogenous abscisic acid (ABA). This may suggest that the 45 kDa protein kinase activity regulated by ABA is involved in the cold-stress response in rice (Komatsu et al, 2001). Studies of ACPK1 from the mesocarp of grape barriers (Vitis vinifera x V. labrusca) revealed that ABA stimulates both the activity of the kinase and mRNA level, but not at the same time.…”
Section: Role In Hormone Responsesmentioning
confidence: 99%